Calcium handling remodeling in dilated cardiomyopathy: From molecular mechanisms to targeted therapies - Yuhan Wang; Tingting Zhou; Jiajing Zhao; Hongjun Zhu; Xiaodong Tan; Jiahao Chen; Zhuojun Zhang; Lijuan Shen; Shu Lu (Channels)
Calcium ions play a crucial role in cardiac excitation-contraction (EC) coupling, and disruptions in Ca2+ homeostasis are a key factor in the development of dilated cardiomyopathy (DCM). This review aims to systematically analyze how structural and functional remodeling of Ca2+-handling proteins drives DCM progression and to evaluate therapeutic strategies targeting these pathways. The movement of intracellular Ca2+, which is regulated by transporters like SERCA2a, ryanodine receptor 2 (RYR2), and L-type Ca2+ channels, affects the heart’s contraction and relaxation. In DCM, both structural and functional changes in the Ca2+-handling machinery—including t-tubule remodeling, modifications to RYR2, and dysregulation of SERCA2a and phospholamban (PLN)—disrupt Ca2+ cycling, worsening systolic dysfunction and ventricular dilation. For instance, reduced affinity of SERCA2a for Ca2+ due to imbalances in the PLN-SERCA2a interaction impairs the heart’s ability to reuptake Ca2+ during diastole. Meanwhile, abnormalities in RYR2 contribute to arrhythmogenic Ca2+ leaks. Targeting these pathways for treatment has two main challenges: too much Ca2+ modulation can cause arrhythmias, while insufficient correction may fail to improve heart contractility. Precision interventions demand structurally resolved targets, such as stabilizing RYR2 closed states or enhancing SERCA2a activity via gene therapy, to address DCM’s heterogeneous pathophysiology. Emerging strategies leveraging t-tubule restoration or isoform-specific L-type channel modulation show promise in normalizing Ca2+ transients and halting adverse remodeling. This review compiles evidence that connects changes in EC coupling components to the progression of DCM and emphasizes the potential benefits of restoring Ca2+ balance as a treatment. By integrating molecular insights with clinical phenotypes, structurally informed Ca2+-targeted therapies could pave the way for personalized DCM management, balancing efficacy with minimized off-target effects.